2017
DOI: 10.7759/cureus.1165
|View full text |Cite
|
Sign up to set email alerts
|

Non-Alcoholic Fatty Liver Disease Association with Cardiac Arrhythmias

Abstract: Non-alcoholic fatty liver disease (NAFLD) has become a public health burden all over the world. A significant percentage of the patients with NAFLD have a co-existing metabolic syndrome that is a risk factor for cardiovascular disease. Clinical as well as epidemiological research shows that NAFLD is not simply related to liver-related morbidity and mortality but is also associated with an elevated risk of coronary heart disease (CHD), irregularities of cardiac function as well as cardiac structure, valvular he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 47 publications
0
7
0
8
Order By: Relevance
“…The importance of further study of this issue is due to the mutual infl uence of non-alcoholic fatty liver disease and cardiovascular disease not only on the prognosis, but also on the tactics of patient management. 14,15,16]. В проведенном G. Musso с соавт.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of further study of this issue is due to the mutual infl uence of non-alcoholic fatty liver disease and cardiovascular disease not only on the prognosis, but also on the tactics of patient management. 14,15,16]. В проведенном G. Musso с соавт.…”
Section: Discussionmentioning
confidence: 99%
“…НАЖБП усугубляет ИР, что приводит к выработке большего количества провоспалительных, прокоагулянтных и профиброгенных медиаторов и способствует развитию структурных нарушений в миокарде и эндотелии. Однако, роль биомаркеров воспаления при НАЖБП и ССЗ изучена недостаточно [14,15,37]. Одно из крупнейших исследований по этому вопросу (Multi-Ethnic Study of Atherosclerosis) [38] показало, что повышение циркулирующего интерлейкина-6 (ИЛ-6) при НАЖБП ассоциировано с заболеваниями сердца и сосудов, особенно с образованием бляшек в коронарных артериях.…”
Section: особенности патогенеза нажбп в контексте кардиоваскулярной коморбидностиunclassified
“…Clinical experience and epidemiological evidences showed that NAFLD-related mortality not only referred to the liver itself, but also companied with the complication such as the increased risk of CHD [33, 34]. NAFLD could aggravate insulin resistance in the body and liver that cause atherosclerotic dyslipidemia, and release a variety of pro-inflammatory, pro-coagulant, and pro-fibrotic mediators, which may play an important role in the pathophysiology of cardiac and arrhythmia complications [33, 35]. Single nucleotide polymorphism (SNP) as a significant genetic factor, plays an important role in the development of NAFLD and CHD [36, 37].…”
Section: Discussionmentioning
confidence: 99%
“…Arrhythmias are one of the main cardiovascular diseases in which NAFLD causes an increased risk. Clinical studies have found that NAFLD is associated with increased frequency of supraventricular and ventricular arrhythmias [30,31]. AF is the most common arrhythmia in these patients with increased risk of NAFLD [32,33].…”
Section: Dıscussıonmentioning
confidence: 99%